Effects of Fluorine on Neutrophil Extracellular Trap Formation through Regulating AMPK/p38 Signaling Pathway. (3rd August 2021) - Song, Yanyan; Zhang, Yue; Zhang, Peijun; Yu, Peng; Shang, Xinchi; Lu, Yuting; Li, Yuehong; Gao, Hang
Abstract : Fluorine is an important trace element that is widely dispersed, and studies showed that fluorine could cause severe toxicity to fish. The aim of this study was to investigate the effects of fluorine on neutrophil extracellular trap (NET) formation in common carp and clarify the possible mechanism. The neutrophils were isolated and exposed to 0.25, 0.5, or 1 mM sodium fluoride (NaF). The results showed that NaF could induce the formation of NETs which exhibited a DNA-based network structure modified with histones and myeloperoxidase (MPO). Furthermore, NaF led to the production of reactive oxygen species (ROS) in neutrophils. Western blot results showed that NaF significantly increased the phosphorylation of AMPK and p38. In addition, our results showed that NaF-induced NET formation could be inhibited by an AMPK or p38 inhibitor. In conclusion, our results showed that NaF induced NET formation in neutrophils through regulation of the AMPK/p38 signaling pathway.